Switch or swap strategy in rheumatoid arthritis patients failing TNF inhibitors? Results of a modified Italian Expert Consensus. (5th October 2018) - Todoerti, Monica; Favalli, Ennio Giulio; Iannone, Florenzo; Olivieri, Ignazio; Benucci, Maurizio; Cauli, Alberto; Mathieu, Alessandro; Santo, Leonardo; Minisola, Giovanni; Lapadula, Giovanni; Bucci, Romano; Gremese, Elisa; et al.
Abstract: Objective: To establish evidence-based and experts' opinion filtered statements on the optimal treatment choice between cycling (switch) and changing mode of action strategies (swap) in RA patients failing TNF inhibitors (TNFis). Methods: The relevant question (switch vs swap) was rephrased into a research question according to the population, intervention, comparison and outcome (PICO) strategy, considering all the available scientific evidence published from the 2013 EULAR set of recommendations up to mid-January 2016. Final statements derived from the retrieved scientific evidence and experts' consensus, with eventual rephrasing through a Delphi method during a national consensus of Italian rheumatologists. Results: From a total of 365 records, 12 studies were finally included. The final statements argued that, until head-to-head comparison data are available, switch and swap can be still considered suitable strategies in RA patients failing first TNFi, even though some data seem to lend more support to a different mode of action-targeted strategy. Conclusion: After failure of first TNFi course, switch and swap can be currently considered as alternative suitable approaches in RA patients.